OPTIMALISASI KEPUASAN NASABAH MELALUI PENGGUNAAN MOBILE BANKING BYOND BY BSI: STUDI KASUS DI BANK SYARIAH INDONESIA KCP PADANG PANJANG - Sarah; Muhammad Al Mighwar (At-Tanmiyah Jurnal Ekonomi dan Bisnis Islam, 2024)
In today's digital era, the transformation of banking services through mobile technology has become an important requirement in increasing customer convenience and satisfaction. The same is the case with this research which aims to analyze the optimization of customer satisfaction through the use of the Byond by BSI mobile banking application with a case study at BSI KCP Padang Panjang. The research method used is descriptive with a qualitative approach, where data is collected through literature studies, interviews with customers and customer service, and Customer Satisfaction Survey (CSS) results. The results showed that the Byond by BSI application provides convenience in transactions, more modern features, and increased security aspects, which overall have a positive impact on customer satisfaction. On the other hand, there are still obstacles such as system disruptions due to maintenance and difficulties for some customers who are less familiar with digital technology. The results of this study contribute to the development of more inclusive and user-friendly mobile banking services.